Development of hydroxyapatite layer on superplastic Ti-6Al-4V for biomaterials applications - Adibah Haneem, Mohamad Dom; Mohd Rosli, Zulkifli (2013)
In this study, HA is embedded onto superplastic Ti-6Al-4V through continuous pressing technique at temperature below the allographic temperature to improve the poor bonding strength obtained by the commercial methods. The cross section morphologies of the HA layer show uniform structure without any delamination or cracks at the interface with the surface hardness of approximately 500±5HV. The EDX and line scan analysis shows that interfacial reaction occur between the HA layer and the substrate. Wear test evaluations show that embedded layer on superplastic Ti-6Al-4V substrate can withstand higher pressure compared to the as-received substrate.